2018
DOI: 10.1016/j.ijpharm.2018.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Interdependence of particle properties and bulk powder behavior of indomethacin in quench-cooled molten two-phase solid dispersions

Abstract: Solid dispersions (SDs) hold a proven potential in formulating poorly water-soluble drugs. The present paper investigates the interfacial phenomena associated with the bulk powder flow, water sorption, wetting and dissolution of the SDs prepared by a modified melt and quench-cooling (QC) method. Poorly water-soluble indomethacin (IND) was QC molten with solubilizing graft copolymer (Soluplus®) or polyol sugar alcohol (xylitol, XYL). The interfacial interactions of SDs with air/water were found to be reliant on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Previous research has shown that indomethacin has extremely poor flow properties by the means of Angle of Repose (AOR) and Hausner's ratio [32]. On inspecting indomethacin drug crystals using digital microscopy ( fig.…”
Section: Bulk Properties Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that indomethacin has extremely poor flow properties by the means of Angle of Repose (AOR) and Hausner's ratio [32]. On inspecting indomethacin drug crystals using digital microscopy ( fig.…”
Section: Bulk Properties Testingmentioning
confidence: 99%
“…IND is a non-steroidal anti-inflammatory drug (NSAID) that inhibits cyclooxygenase (COX-I and COX-II) enzymes non-selectively [31]. IND is deemed practically insoluble in water (0.937e −6 g/mL), moreover, it also exhibits poor flow properties because of its highly irregular crystal habits and inter particulate cohesion [32,33]. Thereby IND was the ideal candidate to test the granulation technique’s applicability for powder bed-based 3D printing (PBF) of drug substances with poor solubility and flow properties.…”
Section: Introductionmentioning
confidence: 99%
“…SD's of IND helps in enhancing the overall solubility in various medias, dissolution studies reveals that as compared to pure drug; solid dispersions showed marked increase in dissolution rate. The improvement in dissolution rate may be due to the formation of molecular dispersion of indomethacin in Ocimum basilicum mucilage, leads to partial miscibility, improving the hydrophilic characteristics of the drug substances through interaction with the mucilage [5,9,11].…”
Section: In Vitro Dissolution Rate Studymentioning
confidence: 99%
“…It is a poorly water soluble antirheumatic agent. In literature attempts has been mase to improve the dissolution rate of indomethacin by various techniques like supersaturable delivery systems such as amorphous self-micellizing solid dispersions (SmSDs) [5] amorphous indomethacin coating with chitosan [6] mesoporous silica nanorods [7], spray drying with silica, polyvinylpyrrolidone (PVP) or 2-hydroxypropyl-β-cyclodextrin (HPβCD) [8] Indomethacin:tromethamine a highly crystalline salt by hot melt extrusion technology [9] melt-electrospun fibers (MSFs) [10], Solid dispersions by modified melt and quench-cooling (QC) method with graft copolymer (Soluplus®) or polyol sugar alcohol (xylitol) [11], microwave assisted in situ amorphization of indomethacin with PVP [12], coamorphous salts of indomethacin-lysine [13] .…”
Section: Introductionmentioning
confidence: 99%